2012
DOI: 10.3390/ijms13056454
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Preparation Method for 5-Aminosalicylic Acid Loaded Eudragit S100 Nanoparticles

Abstract: In this study, solution enhanced dispersion by supercritical fluids (SEDS) technique was applied for the preparation of 5-aminosalicylic acid (5-ASA) loaded Eudragit S100 (EU S100) nanoparticles. The effects of various process variables including pressure, temperature, 5-ASA concentration and solution flow rate on morphology, particle size, 5-ASA loading and entrapment efficiency of nanoparticles were investigated. Under the appropriate conditions, drug-loaded nanoparticles exhibited a spherical shape and smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 36 publications
2
27
1
Order By: Relevance
“…The physical mixtures of the drug with the polymers( fig.1 a&b) resulted in the disappearance of such fusion peak, replaced by broad endothermic signals exhibiting reduced melting endotherm .The presence of endothermic signals in the physical mixtures confirmed that bumadizone crystals still exist in the physical mixtures .This was previously observed in the physical mixture of 5 aminosalicylic acid and piroxicam with Eudragit S100 [50,51] and diflunisal with Eudragit RL100 [52]. For confirmation X-ray diffraction measurements were carried out.…”
Section: Differential Scanning Colorimetery (Dsc)supporting
confidence: 80%
“…The physical mixtures of the drug with the polymers( fig.1 a&b) resulted in the disappearance of such fusion peak, replaced by broad endothermic signals exhibiting reduced melting endotherm .The presence of endothermic signals in the physical mixtures confirmed that bumadizone crystals still exist in the physical mixtures .This was previously observed in the physical mixture of 5 aminosalicylic acid and piroxicam with Eudragit S100 [50,51] and diflunisal with Eudragit RL100 [52]. For confirmation X-ray diffraction measurements were carried out.…”
Section: Differential Scanning Colorimetery (Dsc)supporting
confidence: 80%
“…Retrospectively, a few studies have been conducted and accomplished worldwide. As a tangible example, Hu et al (2012) carried out the research in terms of application of EU S100 and acetone by SAS technique to create EU S100 nanoparticle, and they claimed, to achieve access to normal and integrated nanoparticles with 147 nm diameter in 15 MPa at 37°C. It appears that the results were fully appealing.…”
Section: Evaluation Of Ph and Acidity Of Samples Up To 40 Daysmentioning
confidence: 99%
“…In addition, the increase in pressure augments the diffusion of SCF into the solvent, ensuing supersaturation that subsequently results in small-sized particles. [68][69][70] However, the changes in the pressure had no significant influence on the biological activity of the sensitive molecules such as enzymes. 71…”
Section: Pressurementioning
confidence: 99%
“…In some instances, an increase in temperature results in severe aggregation of the particles with irregular surfaces due to collisions among the microparticles and vice versa. [68][69][70] To this end, the drug loading efficiency in the polymeric carriers is reduced during these conditions due to phase separation, which was articulated in a thermodynamics point of view.…”
Section: Temperaturementioning
confidence: 99%
See 1 more Smart Citation